The Influence of Training and Compensation on the Performance of Bengkulu Province Transportation Service Employees - Pambudi, Ferry Setya (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study, to find out and analyze the effect of training and compensation on employee performance at the Bengkulu Provincial Transportation Service.This research is a causal associative research using a quantitative approach. Causal associative research is research that aims to determine the effect of two or more variables. This study describes the relationship of influencing and being influenced by the variables to be studied. Using a quantitative approach because the data to be used to analyze the relationship between variables is expressed by numbers or a numerical scale.X_1 Training and X_2 Compensation have an influence on Employee Performance (Y), this can be seen in the F test which states the value of F_count>F_table, namely (34,638 > 4.00) and (sig α = 0.000 <0.050), so it can be concluded that H_3 is accepted, meaning that simultaneously the variables Training (X_1) and Compensation (X_2) have a significant influence on Employee Performance (Y) at the Bengkulu Province Transportation Service.From the results of the research conducted, the research conducted in this study showed that Training and Compensation had an effect on Employee Performance (Y) at the Bengkulu Province Transportation Service. It is intended from the Correlation Coefficient and Determination that this study has an influence value of R = 0.756 and a determination of R2 = 0.571 where this research has a variable that is not examined at 0.429 or 42.9%.